Edukasi Mengenal Pembuatan Jahe Instan Sebagai Minuman Penghangat Tubuh - Lia Fikayuniar (Eastasouth Institute, 2023)
This community service goal is one of the tasks of the Tri Dharma of Higher Education, to increase the knowledge of the general public, students, and SMK students with online socialization methods about